The Effects of Donor-Recipient Age and Sex Compatibility in the Outcomes of Deep Anterior Lamellar Keratoplasties - Ong, Hon Shing; Chiam, Nathalie; Htoon, Hla Myint; Kumar, Ashish; Arundhati, Anshu; Mehta, Jodhbir S. (Frontiers in Medicine, 2022)
Purpose Corneal transplantations are the commonest allogenic transplant surgeries performed worldwide. Transplantable grade donor cornea is a finite resource. There is thus an impetus for eye banks to optimize the use of each harvested cornea, and clinicians to minimize the risks of graft rejection and failure. With better survival and lower rejection rates, anterior lamellar keratoplasty has gained popularity as an alternative technique to full-thickness penetrating keratoplasty, for the treatment of corneal stromal diseases. This study evaluated the effects of donor-recipient age- and sex-matching on the outcomes of eyes that had undergone deep anterior lamellar keratoplasty (DALK) surgeries. Design Observational cross-sectional study (national corneal graft registry data). Subjects All DALK surgeries performed in a tertiary ophthalmic hospital over an 11-year period. Methods To analyse the effects of donor-recipient sex-matching, transplantations were classified as “presumed H-Y incompatible” (male donor to female recipient) or “presumed H-Y compatible” (all other donor-recipient sex combinations). For age-matching, differences in donor and recipient ages were calculated. Cox proportional hazards regressions were used to evaluate the influence of donor-recipient sex-matching and age-matching on graft failure and rejection. Main Outcome Measures Rates of graft failure and rejection within each group. Results 401 eyes were included. 271 (67.6%) transplants were presumed H-Y compatible. 29 (7.2%) grafts failed and 9 (2.2%) grafts rejected. There were trends of lower hazard ratios (HRs) in graft failure and rejection in the presumed H-Y compatible group [HRs: 0.59 (95% CI 0.20–1.77, p = 0.34) and 0.93 (95% CI 0.22–3.89, p = 0.926), respectively]. Median difference in age between recipients and donors was 15.0 years (IQR −2.8–34.3). The HRs of graft failure and rejection were not influenced by donor-recipient age [HRs per 1-year increase in age difference: 0.995 (95% CI 0.98–1.01, p = 0.483) and 1.01 (95% CI 0.99–1.03, p = 0.394), respectively]. Conclusion In eyes that had undergone DALK surgeries, no significant influence of donor-recipient sex- or age-matching on graft rejection and failure was observed. Without strong evidence and the limitations of obtaining sample sizes required for an adequately powered study, the benefits of sex- and age-matching of donors and recipients during graft allocation for DALK surgeries is currently inconclusive.